A brief psychological intervention for mothers of children with food allergy can change risk perception and reduce anxiety: Outcomes of a randomized controlled trial. Issue 10 (10th August 2017) - Boyle, R. J.; Umasunthar, T.; Smith, J. G.; Hanna, H.; Procktor, A.; Phillips, K.; Pinto, C.; Gore, C.; Cox, H. E.; Warner, J. O.; Vickers, B.; Hodes, M.
Summary: Background: Mothers of children with food allergy have increased anxiety, which may be influenced by healthcare professionals' communication of risk. Objective: To evaluate a brief psychological intervention for reducing anxiety in mothers of children with food allergy. Methods: Two hundred mothers of children with food allergy were recruited from allergy clinics. A computer‐generated randomization list was used to allocate participants to a single‐session cognitive behavioural therapy intervention including a risk communication module, or standard care. Anxiety and risk perception were assessed at 6 weeks and 1 year. Primary outcome was state anxiety at 6 weeks. Secondary outcomes included state anxiety at 1 year, risk perception at 6 weeks and 1 year, and salivary cortisol response to a simulated anaphylaxis scenario at 1 year. Results: We found no significant difference in the primary outcome state anxiety at 6 weeks, with mean 31.9 (SD 10.2) intervention, 34.0 (10.2) control; mean difference 2.1 (95% CI −0.9, 5.0; P =.17). There was significantly reduced state anxiety at 6 weeks in the intervention group, in the subgroup of participants with moderate/high anxiety at enrolment (103/200, 52%), with mean 33.0 (SD 9.3) intervention, 37.8 (SD 10.0) control; mean difference 4.8 (95% CI 0.9, 8.7; P =.016; Cohen's d effect size 0.50). The psychological intervention also reduced risk perception and salivary cortisol response ( P =.032; effect size 0.36). Conclusion: We found evidence that a brief psychological intervention which incorporates accurate risk information may impact on anxiety, risk perception and physiological stress response in mothers of children with food allergy.